Transmission techniques for 4G systems - Silva, Mario Marques da (Boca Raton, FL. : CRC Press, 2013)
"This book compiles the latest developments in the area of wireless communications for Multimedia Broadcast and Multicast Service (MBMS). Based on years of research and extensive participation in many international projects, the author focuses on the key requirements of the emergent services, with special emphasis on the MBMS. The book describes the fundamentals as well as theory. The transmission, detection techniques, and schemes presented in the chapters are applicable to most digital communication services, including wireless and cellular communication"